Design of sliding mode observer for the estimation of train car positions and in-train forces. Issue 4 (2021) - Bouchama, Hiba Fawzia; Defoort, Michael; Berdjag, Denis; Lauber, Jimmy
Abstract: For the control design of freight trains, the estimation of in-train forces is crucial to avoid safety issues caused by the possible failure of car couplers under excessive stress. However, the in-train forces and the relative positions of adjacent train cars are not directly measurable. To address this issue, this paper designs estimators of train car positions and in-train forces using only locomotive-based measurements. Using the multi-point train model, a cascade structure of robust sliding mode differentiators is developed. It provides finite-time estimation of train car positions and in-train forces. Simulation results illustrate the feasibility of the proposed approach.